PENINGKATAN HASIL BELAJAR PASSING BAWAH BOLA VOLI MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TGT (TEAM GAMES TOURNAMENT) PADA SISWA KELAS XI 2 DI SMAN TARUNA NALA JAWA TIMUR - Farhan, Muhammad; Yudasmara, Dona Sandy; Trinopiansyah, Nade (Jurnal Pedagogik Olahraga, 2024)
This study aims to improve students' skills through the cooperative learning model Team Games Tournament (TGT) in the subject of Physical Education, Sports, and Health (PJOK), specifically on the topic of underhand volleyball passing at SMAN Taruna Nala, East Java. The research procedure uses Action Research in Sports, which includes four stages: planning, implementation, observation, and reflection. This research was conducted over two cycles, with two meetings in each cycle. The Team Games Tournament (TGT) cooperative learning model creates a different learning atmosphere by allowing students to learn through competitive games. The results showed an improvement in learning outcomes as measured by students' mastery scores. In the initial stage (pre-test), only 15% of students achieved the Minimum Mastery Criteria (MMC ≥ 75). After cycle 1, the number of students who met the criteria increased to 41%, and in cycle 2, it reached 78%. This improvement indicates that the Team Games Tournament (TGT) cooperative learning model helps students better understand the material before practice, enhances motor skills, and encourages active participation in learning. Therefore, the implementation of the Team Games Tournament (TGT) model has proven effective in improving underhand volleyball passing skills and is considered a viable alternative for PJOK learning, particularly within the context of the Merdeka Curriculum.